Knowledge and competence with patient safety as perceived by nursing students in the classroom and clinical practice: a cross-sectional study - Altunsoy, Cansu; Dag, Gulten Sucu (Bmc, 2025)
Introduction The importance of patient safety in nursing education is gradually increasing. Nursing educators are responsible for developing nursing curriculum that focuses on the patient safety competencies of the graduates of nursing education. The aim of this study was to evaluate self-perceived knowledge and competencies of nursing students on patient safety in classroom and clinical settings. Method This study was a quantitative, a cross-sectional study. The sample included 294 nursing students in three universities in Northern Cyprus between February and May 2021. Data were collected using a questionnaire that consisted of sociodemographic characteristics, and the Health Professional Education in Patient Safety Survey. Results Perceived knowledge of nursing students on patient safety in the classroom and competence levels in the clinical practice was higher than average and were at similar levels. There was a statistically significant difference between the mean scores obtained from the communicating effectively (p=017) and recognize, respond to and disclose adverse events and close calls subscales of the classroom and clinical practice (p=046). Conclusions To better prepare nurses for practice, nurse educators should harmonize patient safety education in accordance with international standards and develop courses and new educational strategies to eliminate missing information on patient safety.
Keywords: Nursing students; Patient safety; Knowledge; Competence; Education